Corticosteroid refractory sarcoidosis. (September 2020) - Goldman, Chananya; Judson, Marc A.
Abstract: A sarcoidosis patient may be refractory to corticosteroid therapy. This may be because corticosteroids are ineffective in relieving the sarcoidosis patient's symptoms/dysfunction or because the clinician has determined that the risks of corticosteroids outweigh their benefits. Interestingly, when corticosteroids truly fail to improve a sarcoidosis patient's condition, it is very rarely because of failure of the drug as an anti-granulomatous agent; rather, it is usually because the patient's symptoms were unrelated to active sarcoid granulomas. In this manuscript, we review the causes of corticosteroid refractory sarcoidosis. The clinician should consider these causes when confronted with a sarcoidosis patient who is either not responding to corticosteroids, developing corticosteroid side-effects, or is at significant risk of developing such side-effects. We believe that determining the cause of corticosteroid refractory sarcoidosis may aid the clinicians in optimizing the care of sarcoidosis patients and clinical researchers in appropriately stratifying patients for clinical trials. Highlights: True corticosteroid failure is a rare occurrence. True corticosteroid failure is extremely rare with pulmonary sarcoidosis and is most commonly seen with cardiac sarcoidosis, neurosarcoidosis and the lupus pernio form of skin sarcoidosis. Corticosteroid failure most commonly is the result of corticosteroid toxicity or concern of the risk of developing corticosteroid toxicity. The clinician should carefully monitor for the development of corticosteroid toxicity in all patients receiving these medications. Corticosteroid failure commonly occurs when the sarcoidosis patient's symptoms or organ dysfunction is unrelated to granulomatous inflammation from sarcoidosis. This may occur from parasarcoidosis syndromes that do not typically respond to corticosteroids such as small fiber neuropathy, fibrosis from previously active sarcoidosis, or medical conditions completely unrelated to sarcoidosis.